Test method for simulating healing process of crack-containing expansive rock soil

Through the experimental method that simulates the healing process of crack-containing expanded geotechnical soil, the problem that the existing technology is difficult to accurately evaluate the hydraulic characteristics of crack-containing expanded geotechnical soil, the accurate determination of expansion force and permeability coefficient is achieved, and the safety evaluation of the deep disposal of nuclear waste is improved.

CN119715996AActive Publication Date: 2025-03-28NANJING UNIV

Patent Information

Application Number
CN202411839358.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate the hydraulic characteristics of expanded rock and soil containing construction cracks, which affects the safety of deep disposal of nuclear waste.

Method used

The experimental method that simulates the healing process of crack-containing expansion rock-wood was used to simulate construction cracks by setting voids around the sample and pressure chamber, the axial and radial expansion pressures were measured, the permeability coefficient was calculated, and the degree of healing was evaluated by dry density and moisture content distribution tests.

Benefits of technology

This method can effectively solve the problem of difficulty in directly and accurately evaluating the hydraulic characteristics of crack-containing expanded rock and soil, provide accurate measurement of expansion force and permeability coefficient, and improve the accuracy of deep disposal of nuclear waste and safety assessment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715996A_ABST
    Figure CN119715996A_ABST
Patent Text Reader

Abstract

The invention discloses a test method for simulating the healing process of crack-containing expansive rock soil. The test method comprises the following steps: S1, preparing a compaction sample; s2, construction crack simulation; s3, assembling a fracture healing test instrument; s4, testing the expansive force and the permeability coefficient; and S5, testing dry density and moisture content distribution. According to the test method for simulating the healing process of the crack-containing expansive rock soil, gaps are formed around a sample and a pressure chamber, construction cracks are simulated, and axial and radial expansion pressures under different construction cracks are measured by adopting a vertically arranged force sensor and a radially arranged pressure sensor; the permeability coefficient of the crack-containing soil body is determined according to the volume of the injected water, the dry density distribution of the sample is determined by utilizing the water content and dry density test, and the test result can be used for comprehensively evaluating the crack healing degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of buffer materials for high-level radioactive waste disposal repositories, and in particular to a test method for simulating the healing process of expansion rock and soil containing cracks. Background Art

[0002] Many countries use a multi-barrier system for deep underground disposal of radioactive waste, which consists of a radioactive nuclear waste container, a natural geological barrier (surrounding rock), a concrete lining, and sealing / backfill materials. In general, after the sealing / backfill materials are uniaxially compacted into blocks, they are piled between the surrounding rock and the radioactive nuclear waste container, leaving construction gaps between the blocks, between the blocks and the container, and between the blocks and the surrounding rock. These construction gaps account for about 10% of the total tunnel volume. When groundwater in the surrounding rock invades, the compacted blocks will expand and fill the construction gaps, gradually filling the closed preferential seepage channels. Subsequently, they will expand under constant volume conditions, showing a sufficiently high expansion pressure to limit the deformation of the tunnel after the concrete lining fails, and have a sufficiently low permeability coefficient to slow down moisture transfer. Therefore, the expansion force and permeability coefficient of the expansion rock and soil with construction cracks are an important basis for the design and safety assessment of the sealing / backfill materials of the nuclear waste disposal repository.

[0003] At present, the research on the hydraulic behavior of compacted sealing / backfill materials mainly adopts indoor and field test methods. The quantitative relationship between swelling pressure and montmorillonite porosity, swelling rock and soil dry density, montmorillonite effective dry density and montmorillonite initial saturation has been preliminarily established. However, previous studies rarely considered construction cracks. The dry density of the compacted block near the construction cracks after the compacted sealing / backfill materials are hydrated rapidly decreases, causing the distribution of dry density to be uneven. The dry density of the area affected by water is low, while the dry density of the innermost area is high. At this time, it is roughly divided into two areas: one is the compressed area, whose dry density is lower than the average value; the other is the swelling area, whose dry density is lower than the average value. As time goes by, the swelling area will continue to expand, while the compressed area will be compressed by the swelling pressure. As time increases, the dry density gradient will decrease and approach a relatively uniform state. The inhomogeneity of the sealing / backfill materials will in turn affect the overall swelling pressure and permeability coefficient, threatening the safety of the deep underground nuclear waste disposal repository. It is necessary to study the healing process of swelling rock and soil containing construction cracks and the long-term impact on hydraulic behavior.

[0004] In summary, the accurate evaluation of the healing process of expansive rock and soil with construction cracks and the accurate determination of the expansion force and permeability coefficient can provide engineers with a reference for the design of deep underground nuclear waste disposal repositories, and can also provide necessary technical support for the evaluation of the long-term safety of deep underground nuclear waste disposal repositories. So far, no scholar has proposed a standardized testing process and a reasonable evaluation method for this problem. Summary of the invention

[0005] The present invention provides a test method for simulating the healing process of expansive rock and soil containing cracks. The method is easy to implement, has a clear principle, is simple to operate, and has a low cost. It can effectively solve the problem that current technical methods are difficult to directly and accurately evaluate the hydraulic properties of expansive rock and soil containing cracks.

[0006] The technical solution of the present invention is as follows:

[0007] A test method for simulating the healing process of cracked expansive rock and soil, the test method comprising the following steps:

[0008] S1. Compacted sample preparation: Grind the expansive rock and soil sample into powder using a crusher, then add deionized water to the powder to make the powder reach the designed moisture content, then transfer the wetted powder into a sealed bag and seal it for a set time to make the moisture evenly distributed; then, pour the powder into a rigid annular sample preparation mold, and use a press to statically compact the powder to the designed dry density;

[0009] S2, construction crack simulation: trim the sample compacted in step S1 into a smaller diameter; place the pressure chamber on a base with a water inlet and an exhaust port, place porous permeable stone and filter paper at the bottom of the pressure chamber, and then place the trimmed sample on the filter paper, ensuring that the sample is located in the middle of the pressure chamber to simulate the test crack;

[0010] S3. Assembly of the crack healing test instrument: Place filter paper and porous permeable stone on the top of the sample in sequence, then place the upper cap with a drainage / exhaust port and use a threaded rod installed on the bracket to support the upper cap to ensure a constant volume condition; set a force sensor under the pressure chamber to measure the axial expansion force, and arrange a pressure sensor through a lateral drilling hole in the pressure chamber to measure the radial pressure; install an exhaust valve on the exhaust port of the base; install a water inlet valve on the water inlet of the base and connect it to the water pressure / volume controller to measure the permeability coefficient of the sample;

[0011] S4, expansion force and permeability coefficient test: before the test, apply initial axial pressure to the sample through the threaded rod; then open the water inlet valve, wait for the gas in the instrument pipeline to be exhausted, close the exhaust valve, start the water injection test, use the force sensor and pressure sensor to measure the axial and radial pressures of the sample, record the amount of water injected at different times according to the water pressure / volume controller, and calculate the permeability coefficient;

[0012] S5. Dry density and moisture content distribution test: For each construction crack, 7 identical specimens were prepared and water was injected for 0.5, 5, 15, 60, 240, 720 and 2160 hours respectively to analyze the crack healing process; after the set water injection time was reached, the crack-healed specimen was quickly taken out of the pressure chamber and divided into three parts: part I, part II and part III; part I was a ring located on the outer layer, corresponding to the initial pores; part III was a cylinder located in the center; part II was a ring between part I and part III; each part was cut into several soil blocks for the determination of moisture content, dry density, suction and microstructure; among them, the moisture content was determined by drying at 105°C for 24 hours, the dry density was determined by hydrostatic weighing after immersing the soil block in a non-aromatic hydrocarbon liquid, the suction was measured by a cold mirror dew point tensiometer, and the microstructure was determined by mercury intrusion technology; the healing curve of the cracked soil was drawn based on the dry density and moisture content distribution time series data.

[0013] Furthermore, in step S1, the expansive rock and soil sample is ground into powder with a particle size of less than 2 mm, and after adding deionized water, it is stored for 48 hours; the diameter of the rigid annular sample preparation mold is 50 mm, and during the compaction process, the displacement rate of the press is controlled at 0.05 mm / min, and the compacted sample height is 10 mm.

[0014] Furthermore, in step S2, the pressure chamber is made of a stainless steel cylinder with an inner diameter of 50 mm and a thickness of 20 mm, and the height of the pressure chamber is 40 mm.

[0015] Furthermore, the pressure chamber is made of 304 stainless steel.

[0016] Further, in step S4, the initial axial pressure applied by the threaded rod is 0.05 MPa.

[0017] Furthermore, the threaded rod is made of 304 stainless steel.

[0018] Further, in step S5, part I is a ring with an inner diameter and an outer diameter of 40 and 50 mm respectively, part II is a ring with an inner diameter and an outer diameter of 20 and 40 mm respectively, and the remaining cylinder with a diameter of 20 mm is part III.

[0019] Furthermore, the measuring range of the force sensor exceeds 10 kN.

[0020] Furthermore, the measuring range of the pressure sensor exceeds 5 MPa.

[0021] Furthermore, the measurement time interval between the force sensor and the pressure sensor should be less than 30s.

[0022] The principle of the test method for simulating the healing process of cracked expansive rock and soil of the present invention is to simulate construction cracks by setting gaps around the sample and the pressure chamber, measure the axial and radial expansion pressures under different construction cracks by using a vertically arranged force sensor and a radially arranged pressure sensor, determine the permeability coefficient of the cracked soil according to the volume of injected water, and determine the dry density distribution of the sample by using a water content and dry density test, and the test results can be used to comprehensively evaluate the degree of crack healing.

[0023] The test method of the present invention includes specific method steps, which are suitable for the detection of the crack healing process of general expansive rock and soil, wherein step S3 provides a crack simulation method, cutting a pre-made cylindrical sample into a cylinder of a designed diameter, and then placing the cut sample into a pressure chamber to form a pre-designed crack between the sample and the pressure chamber wall; step S4 standardizes the test process of axial and radial expansion pressure and permeability coefficient, which is convenient for effectively testing the hydraulic parameters of the cracked soil under the same test conditions; and step S5 draws the healing curve of the cracked soil according to the dry density and water content distribution time series data, and determines the crack healing process and mechanism. Compared with the existing method for measuring hydraulic parameters of expansive rock and soil, the technical progress of the present invention lies in: focusing on the influence of the crack evolution process, quantitatively testing the changes in axial and radial expansion pressure and permeability coefficient caused by the crack, and evaluating the effect of the crack on the hydraulic performance degradation under long-term operation and the hazards of deep nuclear waste engineering. The technical solution of the present invention is safe and stable, has small sample requirements, and has low implementation costs. The test device used in the test process is easy to build and has good repeatability test effects. Multiple tests can be conducted to make the test method results true and reliable with high accuracy, which has guiding significance for the safe operation of deep underground nuclear waste disposal repositories.

[0024] In summary, the technical solution of the present invention has the following beneficial effects:

[0025] 1) Low test cost. All test devices and materials are common instruments and consumables, which can be recycled and reused, reducing the cost of the test.

[0026] 2) The principle is simple and easy to understand, which is convenient for operators to use. Compared with the traditional test method to study the interface effect of construction cracks, this method directly studies the evolution process of the construction crack interface, which is more conducive to revealing the feedback mechanism between soil and construction cracks.

[0027] 3) Simple operation. No large instruments are used, the instruments are easy to assemble, the test methods are simple and easy to operate, and no professional technicians are required to operate, which reduces manpower and material resources.

[0028] 4) Improved data authenticity. The test equipment is simple and the repeatability test effect is good. Through multiple tests, the test method results can be made true and reliable with high accuracy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of a test instrument used in the test method for simulating the healing process of crack-containing swelling rock and soil of the present invention;

[0030] Figure 2 is the test result of the axial expansion pressure in Example 1;

[0031] Figure 3 is the detection result of the radial expansion pressure in Example 1;

[0032] Figure 4 is the test result of the permeability coefficient in Example 1;

[0033] Figure 5 It is a dry density and moisture content distribution test step in the embodiment, and a specific division of the sample into part I, part II and part III after the cracks are healed.

[0034] Figure 6 It is the water content test result in Example 1;

[0035] Figure 7 is the dry density test result in Example 1;

[0036] Figure 8 is the test result of the axial expansion pressure in Example 2;

[0037] Fig. 9 is the detection result of the radial expansion pressure in Example 2;

[0038] Fig.10 is the test result of the permeability coefficient in Example 2;

[0039] Fig.11 It is the water content test result in Example 2;

[0040] Fig.12 It is the dry density test result in Example 2. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to serve as the basis of the present invention.

[0042] All steps involving basic geotechnical tests in the present invention are strictly carried out with reference to the standard "Standard for Geotechnical Test Methods" (GB / T 50123-2019).

[0043] See also Figure 1The test instrument used in the following embodiments includes a pressure chamber 1, a base 2, a porous permeable stone 3, a filter paper 4, an upper cap 5, and a threaded rod 6; the pressure chamber 1 is placed on the base 2, and a water inlet and an exhaust port are provided on the base 2. The water inlet is provided with a water inlet valve 9, and the exhaust port is provided with an exhaust valve 10; a force sensor 7 is provided below the base 2 for measuring the axial expansion pressure, and a pressure sensor 8 is provided on the side of the pressure chamber 1 for measuring the radial expansion pressure; the shape and size of the porous permeable stone 3, the filter paper 4 and the upper cap 5 are the same as the inner cavity of the pressure chamber 1; the upper cap 5 is provided with a drainage / exhaust port, and a drainage pipe 12 is provided on the drainage / exhaust port; the threaded rod 6 is provided on the bracket and can adjust the height, and the pressure chamber 1 is located directly below the threaded rod 6. During the test, the sample is installed in the pressure chamber 1, and the porous permeable stone 3 and the filter paper 4 are respectively provided at both ends of the sample, and the upper cap 5 covers the upper end of the pressure chamber and is supported by the threaded rod 6; the data of the force sensor 7 and the pressure sensor 8 are read by the data acquisition device 11.

[0044] Embodiment 1:

[0045] In Example 1, the test material used is a buffer material for a deep underground nuclear waste disposal repository in France, which is a compacted mixture of MX80 bentonite from the United States and Callovo-Oxfordian (COx) clay rock from France, in which the construction cracks account for 10% of the total volume. The mass ratio of MX80 bentonite to COx clay rock in the mixture is 3:7, and the clay content of MX80 bentonite and COx clay rock is 86% and 26%, respectively.

[0046] In Example 1, the steps of the test method for simulating the healing process of crack-containing expansive rock and soil are:

[0047] 1. Preparation of compacted samples: Use a crusher to grind MX80 bentonite and COx clay rock into powders with a particle size of less than 2 mm. Then mix the MX80 bentonite and COx clay rock powders in a mass ratio of 3:7 and stir evenly. Then transfer the powders into a sealed bag and seal them for 48 hours to make the moisture distribution even. The moisture content of the mixed powder is 7.7%. Then weigh 42.79 g of powder and pour the powder into a rigid annular sample preparation mold with a diameter of 50 mm. Use the displacement rate of the press to control the powder at 0.05 mm / min to statically compact it to a height of 10 mm. At this time, the diameter and height of the compacted sample are 50 and 10 mm, respectively, and the density is 2.0 g / cm 3 .

[0048] 2. Simulate construction cracks: Trim the compacted sample into a smaller diameter of 47.43 mm. Place the pressure chamber 1 with an internal diameter of 50 mm on a base 2 with a thickness of 30 mm and a water inlet and an exhaust port. Place a porous permeable stone 3 and a filter paper 4 with a diameter of 50 mm at the bottom of the pressure chamber 1. Then place the trimmed sample on the filter paper 4. Use a vernier caliper to continuously adjust the position of the sample so that the sample is located in the middle of the pressure chamber 1. Ensure that the center of the sample coincides with the center of the pressure chamber 1. The distance between the sample and the inner wall of the pressure chamber 1 is 1.28 mm. At this time, the construction crack between the sample and the inner wall of the pressure chamber 1 accounts for 10% of the total volume.

[0049] 3. Assembly of the crack healing test instrument: After the construction crack is set, filter paper 4, porous permeable stone 3 and upper cap 5 are placed on the top of the sample, and the upper cap 5 is supported by a threaded rod 6 to ensure that the height of the sample remains unchanged. A force sensor 7 is placed under the base 2 to measure the vertical expansion force. In addition, a pressure sensor 8 is arranged through the side holes of the pressure chamber to measure the radial pressure. Figure 1 The water inlet of the base 2 is connected to a water pressure / volume controller to measure the permeability coefficient of the sample.

[0050] 4. Expansion force and permeability coefficient test: Before the test, an initial axial pressure of 0.05MPa is applied to the sample through the threaded rod 6 to ensure that the sample maintains good contact with the instrument. In order to simulate the on-site conditions of the nuclear waste disposal repository, a salt solution is prepared according to the chemical composition of the on-site groundwater. The prepared salt solution is placed in the salt solution / deionized water converter. One end of the salt solution / deionized water converter is connected to the water pressure / volume controller, and the other end is connected to the water inlet. Then the water pressure of the water pressure / volume controller is stabilized at 10kPa, the water inlet valve is opened, and the salt solution begins to flow into the bottom of the water pressure chamber from the water inlet valve. After the gas in the instrument pipeline is exhausted, the exhaust valve 10 is closed, and the salt solution begins to be injected into the sample from bottom to top. The force sensor 7 at the bottom of the pressure chamber begins to measure the axial expansion pressure of the sample, Pa=4P / (πD 2 ), where Pa is the axial expansion pressure, P is the force sensor, and D is the sample diameter of 50 mm. Figure 2 As shown in the figure, the axial expansion force first increases rapidly, and then gradually stabilizes after 7.4 hours. The pressure sensor 8 on the side measures the radial expansion pressure, and the sample data is recorded every 30 seconds, as shown in the figure. Figure 3 As shown in the figure, the radial expansion force remains zero within 0.08h, increases rapidly after 0.08h, and gradually stabilizes after 7.5h. At the same time, the amount of water injected into the sample by the water pressure / volume controller at different times is recorded, kw = 4Q / (πD 2 △t), such as Figure 4 As shown in the figure, the permeability coefficient decreases rapidly with the wetting time and gradually stabilizes at 7.5h.

[0051] 5. Dry density and moisture content distribution test: 7 identical specimens were prepared and water was injected for 0.5, 5, 15, 60, 240, 720 and 2160 hours respectively. The crack healing process was analyzed. After the cracks were healed, the specimens were quickly taken out of the pressure chamber and divided into three parts: part I, part II and part III. Figure 5 As shown. Part I corresponds to the initial pores, referring to the rings with inner and outer diameters of 40 and 50 mm, respectively, Part II corresponds to the rings with inner and outer diameters of 20 and 40 mm, respectively, and the remaining cylinders with a diameter of 20 mm belong to Part III. Each part is cut into several pieces for the determination of moisture content and dry density. The moisture content is determined by drying at 105°C for 24 hours, weighing before and after drying, and calculating the moisture content in the wet state w = (mm s ) / m s , where m is the mass of the sample in the humidified state, m s is the mass of the sample under complete drying, such as Figure 6 As shown, the moisture content of part I far from the center is higher, while the moisture content of parts II and III close to the center is lower, showing an obviously uneven distribution. The dry density of the sample was determined by hydrostatic weighing after immersing the soil block in a non-aromatic hydrocarbon liquid (Kerdane) (Bian, X., Cui, YJ & Li, XZ 2019b. Voids effect on the swelling behavior of compacted bentonite. Géotechnique 69, No. 7, 593-605), and the dry density of the sample ρ was calculated. d =m s ρ k / (mm k ), where m is the mass of the sample in the humidified state, m s is the mass of the sample when completely dried, m k is the mass after immersion in non-aromatic hydrocarbon liquid (Kerdane); ρ k is the dry density of the non-aromatic hydrocarbon liquid. As shown in 7, the dry density of part I far from the center is small, which is less than the average dry density of the sample 1.8Mg / m 3 , while the moisture content of Part II and Part III, which are close to each other, is relatively high, showing an obviously uneven distribution.

[0052] Embodiment 2:

[0053] The test material used in Example 2 is also a compacted mixture of MX80 bentonite from the United States and Callovo-Oxfordian (COx) clay rock from France, in which the construction cracks account for 20% of the total volume.

[0054] The steps of the test method for simulating the healing process of crack-containing expansive rock and soil in Example 2 are:

[0055] 1. Preparation of compacted samples: Use a crusher to grind MX80 bentonite and COx clay rock into powders with a particle size of less than 2 mm. Then mix the MX80 bentonite and COx clay rock powders in a mass ratio of 3:7 and stir evenly. Then transfer the powders into a sealed bag and seal them for 48 hours to make the moisture distribution even. The moisture content of the mixed powder is 7.7%. Then weigh 42.79 g of powder and pour the powder into a rigid annular sample preparation mold with a diameter of 50 mm. Use the displacement rate of the press to control the powder at 0.05 mm / min to statically compact it to a height of 10 mm. At this time, the diameter and height of the compacted sample are 50 and 10 mm, respectively, and the density is 2.0 g / cm 3 .

[0056] 2. Construction crack simulation: In order to simulate 20% construction cracks, the compacted sample is trimmed into a smaller diameter of 44.72mm. The pressure chamber 1 with an internal diameter of 50mm is placed on a base 2 with a thickness of 30mm and a water inlet and an exhaust port. At the bottom of the pressure chamber 1, a porous permeable stone 3 with a diameter of 50mm and a filter paper 4 are placed in sequence. Then the trimmed sample is placed on the filter paper 4. The position of the sample is continuously adjusted using a vernier caliper so that the sample is located in the middle of the pressure chamber, ensuring that the center of the sample coincides with the center of the pressure chamber, and the distance between the sample and the inner wall of the pressure chamber is 2.64mm. At this time, the construction cracks between the sample and the inner wall of the pressure chamber account for 20% of the total volume.

[0057] 3. Assembly of the crack healing test instrument: After the construction crack is set, filter paper 4, porous permeable stone 3 and upper cap 5 are placed on the top of the sample, and the upper cap 5 is supported by a threaded rod 6 to ensure that the height of the sample remains unchanged. A force sensor 7 is set under the base 2 to measure the vertical expansion force, and a pressure sensor 8 is arranged through the lateral drilling hole of the pressure chamber to measure the radial pressure. The water inlet hole of the base is connected to the water pressure / volume controller to measure the permeability coefficient of the sample.

[0058] 4. Expansion force and permeability coefficient test: Before the test, an initial axial pressure of 0.05MPa is applied to the sample through the threaded rod 6 to ensure that the sample maintains good contact with the instrument. In order to simulate the on-site conditions of the nuclear waste disposal repository, a salt solution is prepared according to the chemical composition of the on-site groundwater. The prepared salt solution is placed in the salt solution / deionized water converter. One end of the salt solution / deionized water converter is connected to the water pressure / volume controller, and the other end is connected to the water inlet. Then the water pressure of the water pressure / volume controller is stabilized at 10kPa, the water inlet valve is opened, and the salt solution begins to flow into the bottom of the water pressure chamber from the water inlet valve. After the gas in the instrument pipeline is exhausted, the exhaust valve is closed, and the salt solution begins to be injected into the sample from bottom to top. The force sensor at the bottom of the pressure chamber begins to measure the axial expansion pressure of the sample, Pa=4P / (πD 2), where Pa is the axial expansion pressure, P is the force sensor, and D is the sample diameter of 50 mm. Figure 8 As shown in the figure, the axial expansion force first increases rapidly, reaches a peak of 0.80 MPa at 0.68 h, then gradually decreases and gradually stabilizes after 5.8 h. The pressure sensor on the side measures the radial expansion pressure, and the sample data is recorded every 30 seconds, as shown in the figure. Fig. 9 As shown in the figure, the radial expansion force remains zero within 0.18h, increases rapidly after 0.18h, and gradually stabilizes after 5.7h. At the same time, the amount of water injected into the sample by the water pressure / volume controller at different times is recorded, kw = 4Q / (πD 2 △t), such as Fig.10 As shown in the figure, the permeability coefficient decreases rapidly with the wetting time and gradually stabilizes at 5.8h.

[0059] 5. Dry density and moisture content distribution test: 7 identical specimens were prepared and water was injected for 0.5, 5, 15, 60, 240, 720 and 2160 hours respectively. The crack healing process was analyzed and the specimens were quickly taken out of the pressure chamber after crack healing and divided into three parts: Part I, Part II and Part III. Part I corresponds to the initial pores, which refers to the ring with an inner diameter and an outer diameter of 40 and 50 mm respectively. Part II corresponds to the ring with an inner diameter and an outer diameter of 20 and 40 mm respectively. The remaining cylinder with a diameter of 20 mm belongs to Part III. Each part was cut into several soil blocks for determining the moisture content and dry density. The moisture content was determined by drying at 105°C for 24 hours. The weight was weighed before and after drying, and the moisture content w in the wet state was calculated to be (mm s ) / m s , where m is the mass of the sample in the humidified state, m s is the mass of the sample under complete drying, such as Fig.11 As shown, the moisture content of part I far from the center is higher, while the moisture content of parts II and III close to the center is lower, showing an obviously uneven distribution. The dry density of the sample was determined by hydrostatic weighing after immersing the soil block in a non-aromatic hydrocarbon liquid (Kerdane) (Bian, X., Cui, YJ & Li, XZ 2019b. Voids effect on the swelling behavior of compacted bent onite. Géotechnique 69, No. 7, 593-605), and the dry density of the sample ρ was calculated. d =m s ρ k / (mm k ), where m is the sample mass in the humidified state, m s is the mass of the sample when completely dried, m k is the mass after immersion in non-aromatic hydrocarbon liquid (Kerdane); ρk is the dry density of the non-aromatic hydrocarbon liquid. As shown in 12, the dry density of part I far from the center is smaller, which is less than the average dry density of the sample 1.6Mg / m 3 , while the moisture content of Part II and Part III, which are close to each other, is relatively high, showing an obviously uneven distribution.

[0060] The above general description of the invention involved in this application and the description of its specific implementation methods should not be understood as limiting the technical solutions of the invention. Based on the disclosure of this application, those skilled in the art can add, reduce or combine the disclosed technical features in the above general description and / or specific implementation methods (including examples) without violating the constituent elements of the invention involved, to form other technical solutions within the scope of protection of this application.

Claims

1. A test method for simulating the healing process of expansive rock and soil containing cracks, characterized in that: The test method includes the following steps: S1. Compacted sample preparation: Grind the expansive rock and soil sample into powder using a crusher, then add deionized water to the powder to make the powder reach the designed moisture content, then transfer the wetted powder into a sealed bag and seal it for a set time to make the moisture evenly distributed; then, pour the powder into a rigid annular sample preparation mold, and use a press to statically compact the powder to the designed dry density; S2, construction crack simulation: trim the sample compacted in step S1 into a smaller diameter; place the pressure chamber (1) on a base (2) having a water inlet and an exhaust port, place a porous permeable stone (3) and a filter paper (4) at the bottom of the pressure chamber (1), and then place the trimmed sample on the filter paper, ensuring that the sample is located in the middle of the pressure chamber to simulate the test crack; S3. Assembly of the crack healing test instrument: Filter paper (4) and porous permeable stone (3) are placed on the top of the sample in sequence, and then an upper cap (5) with a drainage / exhaust port is placed and a threaded rod (6) installed on the bracket is used to support the upper cap (5) to ensure a constant volume condition; a force sensor (7) is arranged below the pressure chamber (1) to measure the axial expansion force, and a pressure sensor (8) is arranged by drilling a hole on the side of the pressure chamber (1) to measure the radial pressure; an exhaust valve (10) is installed at the exhaust port of the base (2); an inlet valve (9) is installed at the water inlet of the base (2) and connected to a water pressure / volume controller to measure the permeability coefficient of the sample; S4, expansion force and permeability coefficient test: before the test, an initial axial pressure is applied to the sample through the threaded rod (6); then the water inlet valve (9) is opened, and after the gas in the instrument pipeline is exhausted, the exhaust valve (10) is closed, and the water injection test is started. The axial and radial pressures of the sample are measured using a force sensor (7) and a pressure sensor (8), and the amount of water injected at different times is recorded by a water pressure / volume controller to calculate the permeability coefficient; S5. Dry density and moisture content distribution test: For each construction crack, 7 identical samples were prepared and water was injected for 0.5, 5, 15, 60, 240, 720 and 2160 hours respectively to analyze the crack healing process; after reaching the set water injection time, the crack-healed sample was quickly taken out from the pressure chamber (1) and divided into three parts: part I, part II and part III; part I is the ring located in the outer layer, corresponding to the initial pores; Part III is a cylinder located in the center; Part II is a ring between Part I and Part III; each part is cut into several soil blocks for determining moisture content, dry density, suction and microstructure; the moisture content is determined by drying at 105°C for 24 hours, the dry density is determined by hydrostatic weighing after immersing the soil blocks in non-aromatic hydrocarbon liquid, the suction is measured by a cold mirror dew point tensiometer, and the microstructure is determined by mercury injection technology; the healing curve of the cracked soil is drawn based on the dry density and moisture content distribution time series data.

2. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 1, characterized in that: In step S1, the expansive rock and soil sample is ground into powder with a particle size of less than 2 mm, and after adding deionized water, it is stored for 48 hours; the diameter of the rigid annular sample preparation mold is 50 mm, and during the compaction process, the displacement rate of the press is controlled at 0.05 mm / min, and the compacted sample height is 10 mm.

3. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 2, characterized in that: In step S2, the pressure chamber (1) is made of a stainless steel cylinder with an inner diameter of 50 mm and a thickness of 20 mm, and the height of the pressure chamber (1) is 40 mm.

4. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 3 is characterized in that: The pressure chamber is made of 304 stainless steel.

5. The test method for simulating the healing process of cracked expansive rock and soil according to claim 4, characterized in that: In step S4, the initial axial pressure applied by the threaded rod (6) is 0.05 MPa.

6. The test method for simulating the healing process of cracked expansive rock and soil according to claim 5, characterized in that: The threaded rod (6) is made of 304 stainless steel.

7. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 6, characterized in that: In step S5, part I is a ring with an inner diameter and an outer diameter of 40 and 50 mm respectively, part II is a ring with an inner diameter and an outer diameter of 20 and 40 mm respectively, and the remaining cylinder with a diameter of 20 mm is part III.

8. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 7, characterized in that: The measuring range of the force sensor (7) exceeds 10 kN.

9. The test method for simulating the healing process of expansive rock and soil containing cracks according to claim 8, characterized in that: The measuring range of the pressure sensor (8) exceeds 5 MPa.

10. The test method for simulating the healing process of cracked expansive rock and soil according to claim 7, 8 or 9, characterized in that: The measurement time interval between the force sensor (7) and the pressure sensor (8) should be less than 30 seconds.

Citation Information

Patent Citations

  • Engineering barrier system self-sealing and healing property measurement testing device

    CN106546710A

  • Concrete-high-compaction bentonite composite system behavior simulation test method and device

    CN109187213A

  • Bentonite block single joint healing effect testing device and method

    CN111610315A

  • Bentonite permeation-diffusion-expansive force combined test device and test method thereof

    CN113155701A

  • Apparatus and Method for Evaluating Crack Width and Self-healing Performance of Cracked Concrete Specimen

    KR102105840B1

Cited By

  • Expansion force anisotropy testing device for bentonite construction joint self-healing

    CN120558720A

  • Device for jointly testing leakage amount and expansion stress at lap joint of geomembrane vertical barrier and testing method thereof

    CN120594356A